Pertumbuhan dan Hasil Jagung Akibat Pemberian Pupuk Organik dan Effective Microorganisms-4 (Em-4) - Munazar; Zurrahmi Wirda; Jamidi; Usnawiyah (Jurnal Multidisiplin Madani, 2022)
This study aims to determine the effect of organic fertilizer and EM-4 and the interaction between the two on the growth and yield of maize. The study used a factorial randomized block design. The experimental factors studied were the factor of giving organic fertilizer and the factor of giving EM-4. Observations included plant height, number of leaves, number of cobs per plant, weight of cobs per plant and weight of 100 seeds. The results showed that the manure treatment had a significant effect on plant height at the age of 6 WAP. EM4 treatment had a significant effect on the weight of the cobs per plant. There was a very significant interaction between the treatment of manure and EM4 on plant height at the age of 6 WAP and a significant interaction with the number of leaves at the age of 4 and 6 WAP.